I know what it is but how bad does it get? Insights into the lived experience and service needs of people with early-stage dementia - Begley, Emer (Trinity College (Dublin, Ireland). Department of Sociology, 2009)
In Ireland, age-related illnesses such as dementia are becoming a greater policy concern in line with population ageing. Despite this, dementia-specific policies and practices are still largely under-developed and the preferences and thoughts of people living with dementia are rarely sought. This thesis provides insights into the lived experiences, the health and social care needs and service utilisation of people living with early-stage dementia. It links the 'personal' to the 'political' by placing their experiences within a framework of the Irish health and social care system, hence embedding the personal, lived experiences within the systemic context.
Keywords: Social Studies, Ph.D.; Ph.D. Trinity College Dublin